The More Economic Approach to Exclusionary Abuses Under Article 102 TFEU - Dimitrova, Emilia (Yearbook of the Law Department, 2022)
The present paper examines in a comparative legal aspect the more economic approach in the ‘rule of reason’ doctrine, formulated in connection with the implementation of the American antitrust legislation, and the approach defined in the Guidelines on the application of Article 102 TFEU to exclusionary abuses, adopted by the European Commission. The purpose of the comparative legal research is to establish whether the approach taken by the European Commission to exclusionary abuses follows the analytical model of the ‘rule of reason’ doctrine.